Triple X syndrome: a rare case entity with premature ovarian failure, recurrent abortion and secondary infertility - Soni, Savita; Nadkarni, Purnima; Nadkarni, Kishore; Nadkarni, Aditi; Tanksale, Shreedevi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Triple X syndrome is a sex chromosome abnormality characterised by extra X chromosome, occurring in 1 in 1000 female births. This condition often remains undiagnosed as most of them have normal phenotype, puberty and fertility. We report a case of Triple X syndrome with normal phenotype and intelligence presented with premature ovarian failure, recurrent abortion and secondary infertility. This case emphasizes the need for chromosomal analysis in women presenting with premature ovarian failure leading to recurrent abortion and secondary infertility.